The reception of asylum seekers under international law : between sovereignty and equality - Slingenberg, Lieneke (Studies in international law (Oxford, England), 2014)
The European Union is currently engaged in a process of developing minimum conditions for the reception of asylum seekers, as part of a Common European Asylum System. This book critically examines the outcomes of the negotiation process.